(untitled) (Research, Society and Development, 2021)
The coating mortars behavior in its fresh state has been the object of many recent researches in Brazil. It has become, therefore, interesting the introduction of new technologies, which seek to optimize the performance of mortars, improving the knowledge of its properties, allowing a productive enforcement and minimizing, overall, future failures. The article analyzes the coating mortars’ behavior, in its fresh state, verifying the efficiency in the use of the direct shear equipment, with different combinations of traces and composing materials. Four traces of mortar were dosed, with distinct proportions of lime (TR1 = 1:0:6; TR2 = 1:0,5:6; TR3 = 1:1:6 – reference; TR4 = 1:1,5:6), presenting constant scattering (flowtable) and equal to 245 ± 5 mm. Direct shear assays were done applying different normal tensions (10 kPa, 37 kPa and 50 kPa) and shear speed of 0,2 mm/min. The method allowed to identify increase of shear tensions, cohesion, friction angle and horizontal displacements as lime is added on the mixture, indicating the sensibility of the method and great potential of use to this appraisal in mortar in its fresh state. The addition of lime in traces increases the water/cement factor for the same workability in the fresh state, but in the hardened state it can increase the porosity of mortar, causing loss of RCS. Eletromicrografhs made it possible to identify the pores, the arrangements between the constituents, the roughness of the surfaces, the interface areas between materials and the crystals present in the binder paste.